(untitled) (Emancipação, 2026)
There is a global trend towards the incorporation of the SDGs in higher education in the signatory countries of the 2030 Agenda approved in 2015. Different issues can be addressed and deepened in this sense in various aspects such as teaching, research, extension and governance. The general objective of this article is to analyze how plans and actions in sustainability and sustainable development are being developed in the seven state universities of Paraná in the scope of management and in the aspects of teaching, research and extension. The methodology used was qualitative, with content analysis through documentary research of the institutional development plans (IDPs) and seven semi-structured interviews with institutional representatives. The data collected indicate that universities are in different phases in the implementation and execution of the 2030 Agenda, that human and financial resources are incipient for the demand, and that the basis of implementation is being developed partially through partnerships. It can be inferred the existence of two clusters, the first being advanced universities and those in the beginning of the process. This article can contribute to the understanding of the theme, insights for plans and projects of universities, in favor of the sustainable development goals.